2001
DOI: 10.1148/radiol.2211001563
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Infarction in Humans with23Na MR Imaging: Comparison with Cine MR Imaging and Delayed Contrast Enhancement

Abstract: (23)Na MR imaging demonstrates dysfunctional myocardium caused by subacute and chronic myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…The endo-and epicardial borders, as well as the borders of the areas with elevated 23 Na SI, were traced manually with the use of ARGUS software version VB31B (Siemens AG, Germany). The mass of the area with elevated 23 Na SI was obtained by summing the volume for each slice, and expressed as a percentage of the total LV muscle mass (12). For evaluation of 23 Na SI, the SIs of the infarcted area and the entire noninfarcted myocardium, as well as noise, were measured for each slice separately by region-of-interest (ROI) analysis, and expressed as the mean and standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endo-and epicardial borders, as well as the borders of the areas with elevated 23 Na SI, were traced manually with the use of ARGUS software version VB31B (Siemens AG, Germany). The mass of the area with elevated 23 Na SI was obtained by summing the volume for each slice, and expressed as a percentage of the total LV muscle mass (12). For evaluation of 23 Na SI, the SIs of the infarcted area and the entire noninfarcted myocardium, as well as noise, were measured for each slice separately by region-of-interest (ROI) analysis, and expressed as the mean and standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, we were able to show that 1) cardiac 23 Na MRI can be applied in humans, 2) the myocardium/blood 23 Na signal intensity (SI) ratio represents the ratio of the 23 Na concentrations in myocardium and blood, and 3) 23 Na SI is elevated in MI (10,11). A comparison of 23 Na MRI with 1 H MRI techniques in patients with subacute or chronic MI, respectively, revealed an area of elevated 23 Na SI that significantly correlated with wall motion abnormalities, as detected by cine MRI, in all patients after subacute MI and 80% of patients with chronic MI (12). Myocardial edema in subacute MI also correlated with the areas of elevated 23 Na SI, but it was extensively larger, whereas a significant correlation of late enhancement with 23 Na MRI was found only in the subacute group.…”
mentioning
confidence: 99%
“…Short-axis views were applied to detect changes in tissue integrity in LV myocardium. 13 To detect late enhancement, images were acquired 10 to 15 minutes after the injection of gadopentetate dimeglumine (Magnevist, Schering, Berlin, Germany; 0.2 mmol/kg body weight) by use of an inversion recovery sequence (field of view, 240ϫ320 mm 2 ; matrix, 165ϫ256). All LV segments were evaluated for the presence of myocardial fibrosis according to the standardized nomenclature for imaging of the heart.…”
Section: Cmri Studiesmentioning
confidence: 99%
“…Due to lower MR detection sensitivity and lower in vivo concentration (9.3% and 0.05% relative to 1 H), the major limitation of 23 Na MR is the reduced signal-tonoise ratio (SNR) compared with 1 H MR. 23 Na MR, however, allows noninvasive insight into regional cellular ion homeostasis while 1 H MRI does not. In vivo and in vitro animal and human clinical studies demonstrated the feasibility of detecting location and quantifying myocardial infarction (2)(3)(4)(5).…”
mentioning
confidence: 99%